"I bit you or I beat you?" Acoustic analysis of vowel contrast produced by Malay speakers - Wan Ahmad, Wan Aslynn Salwani; Pillai, Stefanie (2016)
This paper examines the acoustic properties of two pairs of English vowels: /i:/, /ɪ/ and /u:/,/ʊ/ produced by two sets of Malay speakers. This study was motivated by claims that Malaysian English (MalE) speakers do not distinguish these vowels’ phonemic lengths. The data was obtained from the recordings of five Malay informants. The recordings were instrumentally analysed, in which the durations, first (F1) and second formants (F2) of these vowels were measured. The formant values were obtained to describe vowel height and vowel fronting/ retraction of each vowel. Consistent with previous studies, the findings indicate that these speakers did not distinguish vowel quality and vowel length of these vowels. The formant values of these two sets of vowels show that /i:/ and /ɪ/ and /u:/,/ʊ/, have similar qualities in terms of vowel height and fronting or retraction, resulting in a smaller inventory of monophthong vowels for MalE.